Pengaruh Pijat Ibu Hamil Terhadap Tingkat Kecemasan Menghadapi Persalinan Pada Ibu Primigravida Trimester III Di PMB Nopi Utami Tangerang : The Effect of Pregnant Women's Massage on the Level of Anxiety in Facing Childbirth in Primigravida Trimester III Mothers at PMB Nopi Utami Tangerang - Yovika; Tridiyawati, Feva (Dohara POAJ, 2023)
Introduction: Anxiety in facing childbirth in primigravida mothers often occurs. The prevalence of anxiety in Indonesia is 28,7% of 107,000,000 third-trimester pregnant women experiencing anxiety in facing childbirth. The way to deal with anxiety is non-pharmacological therapy, one of which is massage for pregnant women. Methods: Using a quasi-experiment with a pretest and posttest group design means that the researcher made observations before and after the intervention without a control group. The sampling technique used was purposive sampling with a total sample of 30 respondents. Nominal and ordinal scale data variables were analyzed data with the Wilcoxon test with α ₌ 0,05. Results: Showing the effect of massage for pregnant women on the level of anxiety facing childbirth in third-trimester primigravida women with test analysis Wilcoxon obtained a significance value of 0,000 (p < 0,05) and it can be concluded, there is a significant difference the effect of massage for pregnant women on reducing the level of anxiety of pregnant women facing labor before and after being given a massage for pregnant women. Discussion: There is a significant difference in the effect of massage for pregnant women on reducing the level of anxiety of pregnant women in facing labor before and after the intervention. Pregnant women who do massage will get a relaxing effect and prevent excessive anxiety during pregnancy.